PENGARUH GAYA HIDUP DAN HARGA TERHADAP MINAT BELI PAKAIAN THRIFTING DI PASAR PAGI MINGGU KOTA BANJARMASIN - Alma Puteri Hafsari; Nurul Wahyuni; Siti Rusidah; Novia Nour Halisa (Smart Business Journal (SBJ), 2025)
This study aims to examine the influence of lifestyle and price on the purchase intention of thrifting clothes, both partially and simultaneously. This research uses a quantitative explanatory method. The study was conducted at Pasar Pagi Minggu in Banjarmasin City, involving 100 respondents selected through accidental sampling. Data were collected using questionnaires and analyzed with multiple linear regression. The results show that lifestyle has a positive and significant partial effect on purchase intention, and price also has a positive and significant partial effect on purchase intention. Simultaneously, both lifestyle and price have a significant influence on the purchase intention of thrifting clothes at Pasar Pagi Minggu in Banjarmasin City.